Don't put all your legs in one basket: theory and evidence on coopetition in road cycling - Matthes, Julian; Piazolo, David (AWI discussion paper series, 2024)
Road cycling races, although won by individual riders, are a competition of teams. Riding behind other riders significantly reduces the energy required to hold a given speed. These races thus provide free-riding incentives. We introduce a game-theoretic framework of this strategic setup to analyze a team's winning probability in various race situations and to examine group characteristics facilitating coordination. We complement our theoretical results with an empirical analysis using data from more than 40 seasons of professional road cycling races. Our model suggests that asymmetry in rider strength or team strength within a group is favorable for group coordination. Also, adding teammates to competing groups is beneficial because it leads to strategic benefits, increasing the free-riding opportunities in both groups. We find empirical evidence that a teammate in a group behind has a positive impact on win probability, indicating that such an effect indeed exists.